2016
DOI: 10.1038/srep26406
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-Connecting and Lone-Electron-Pair Active Trigonal-Pyramidal-AsO3 Inducing Nanosized Poly(polyoxotungstate) Aggregates and Their Anticancer Activities

Abstract: By virtue of the stereochemical effect of the lone-electron pair located on the trigonal-pyramidal-AsO3 groups and the one-pot self-assembly strategy in the conventional aqueous solution, a series of novel lanthanide-bridging and lone-electron-pair active trigonal-pyramidal-AsO3 inducing nanosized poly(polyoxotungstate) aggregates [H2N(CH3)2]6 Na24H16{[Ln10W16(H2O)30O50](B-α-AsW9O33)8}·97H2O [Ln = EuIII (1), SmIII (2), GdIII (3), TbIII (4), DyIII (5), HoIII (6), ErIII (7), TmIII (8)] were prepared and further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 54 publications
(60 reference statements)
0
18
0
2
Order By: Relevance
“…However, in the physiological solutions (pH 7.0–7.5), for most bioanalytical applications, the POM nanozymes become catalytically inactive. Fortunately, POMs show a great diversity in its structure derived from its multiple oxidation states and coordination geometries 30,34 . These features make it much easier to control the size, shape, and charge distribution at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the physiological solutions (pH 7.0–7.5), for most bioanalytical applications, the POM nanozymes become catalytically inactive. Fortunately, POMs show a great diversity in its structure derived from its multiple oxidation states and coordination geometries 30,34 . These features make it much easier to control the size, shape, and charge distribution at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that Ln-based compounds, with the merits of a narrow emission line as well as high color purity, are endowed with broad application prospects in light-emitting diodes, biosensing technologies, imaging techniques, and waveguide amplifiers. It can be clearly observed that the emission spectrum of 1 upon 388 nm excitation (Figure a) displays four characteristic emission bands caused by Dy 3+ f–f transitions, where two strong emission bands centered at 480 and 575 nm are attributed to the magnetic dipole transition ( 4 F 9/2 → 6 H 15/2 ) and the electric dipole transition ( 4 F 9/2 → 6 H 13/2 ); the other two weak emission bands are centered at 662 nm ( 4 F 9/2 → 6 H 11/2 ) and 749 nm ( 4 F 9/2 → 6 H 9/2 ). , The intensity of the F 9/2 → 6 H 13/2 transition is higher than that of the 4 F 9/2 → 6 H 15/2 transition, indicating that Dy 3+ ions in 1 occupy the lattice site without inversion symmetry. , An excitation band of O → W ligand-to-metal-charge transfer (LMCT) and five distinct peaks at 270, 353, 367, 388, 430, and 453 nm appearing in the excitation spectrum of 1 (Figure S10a) are assigned to the 1 A 1g → 1 T 1u transition of AT ligands and 6 H 15/2 to 6 P 7/2 , 6 P 5/2 , 4 I 13/2 , 4 G 11/2 , and 4 I 15/2 transitions of Dy 3+ ions. , The lifetime decay profile of 1 (monitoring upon 574 nm emission) (Figure b) fits well using a second-order exponential equation, resulting in lifetimes of τ 1 = 2.53 μs (29.93%) and τ 2 = 14.80 μs (70.07%), and the average vaule (τ*) is 11.13 μs, similar to results from a previous report . Compound 2 emits orange luminescence upon 454 nm excitation, and three featured emission peaks located at 551, 581, and 660 nm appear in the range 540–750 nm (Figure c) and are, respectively, ascribed to Ho 3+ 5 F 4 + 5 S 2 → 5 I 8 , 5 G 6 + 5 F 1 → 5 I 7 , and 5 F 5 → 5 I 8 transitions.…”
Section: Resultsmentioning
confidence: 99%
“…Penggunaannya dalam mikroelektronika (19)(20)(21) ditemukan meningkat. NF3 ini merupakan suatu molekul dengan bentuk molekul piramidal trigonal (23)(24)(25)(26) . NF 3 sedikit larut dalam air yaitu 0,021 g/100 ml tanpa mengalami reaksi kimia (235) .…”
Section: Kesimpulanunclassified
“…Penggunaannya dalam mikroelektronika (19)(20)(21) ditemukan meningkat. NF 3 ini merupakan suatu molekul dengan bentuk molekul (22) piramidal trigonal (23)(24)(25)(26) . Pada NF 3 ini terdapat beberapa parameter transfor elektron (10) (Koefisien Townsend (10) , koefisien disosiatif (10) , koefisien fraksi disosiatif (10) , fraksi energi elektron yang hilang akibat tabrakan dengan NF 3 (10) , mobilitas elektron (10) dan kecepatan drift (10) ) gas NF3 ini.…”
Section: Introductionunclassified